Implementation of digital marketing in Khoirul’s business: Topup via Instagram acccount as an effective promotional medium - Sakina Sudin; Sutisna Jayaatmaja; Muhammad Khoirul Anam; Muhammad Irmanto; Algifahri Suhaeman (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The digital transformation of micro, small, and medium enterprises (MSMEs) represents a critical evolution in contemporary business ecosystems, particularly within emerging economies. Indonesia exemplifies this phenomenon, where digital marketing adoption has accelerated dramatically, with approximately 74.6% of the population actively using the internet and 191.4 million citizens engaging with social media platforms as of early 2025 (We Are Social, 2024). This proliferation of digital connectivity has fundamentally reconfigured marketing paradigms, enabling MSMEs to transcend geographical constraints and access previously unreachable market segments (Putra & Arifin, 2021). Research indicates that Indonesian MSMEs implementing structured digital marketing strategies report sales increases of 20-30% within the first year of adoption, while simultaneously reducing promotional expenditures by up to 70% (Tambunan & Busnetti, 2024; Utomo, 2024). The strategic integration of digital technologies has become indispensable for business survival and competitive positioning, particularly as the post-pandemic economic landscape demands greater operational resilience and market adaptability. Among available digital platforms, Instagram has emerged as the dominant marketing channel for Indonesian MSMEs, commanding 84.8% user penetration and offering sophisticated features for visual storytelling, direct customer engagement, and transactional facilitation (We Are Social, 2024). The platform's visual-centric architecture supports diverse content formats including feeds, stories, reels, and direct messaging, which collectively enable businesses to construct compelling brand narratives and foster interactive consumer relationships (Jenifer & Nawangpalupi, 2024). Empirical evidence demonstrates that Instagram marketing activities significantly enhance brand awareness and consumer engagement, with creative content strategies correlating strongly with purchase intention (Karuehni, 2024; Rahman, 2022). Ahmad (2021) further confirms that Instagram Ads increase brand awareness by 65% when deployed with precise audience targeting xand engaging visual content, while Nugraha (2022) documents that consistent posting, interactive stories, and promotional giveaways substantially elevate brand recognition and customer acquisition for culinary MSMEs. Despite these promising indicators, a substantial implementation gap persists between digital marketing potential and actual practice among Indonesian micro-enterprises. Putri (2023) reveals that many MSMEs in Bandung continue relying on conventional promotional methods, limiting market reach and growth trajectory. This reluctance stems from multifaceted barriers including limited digital literacy, resource constraints, and inadequate understanding of strategic content planning (Purnamasari, 2024). Yusuf and Andini (2024) identify that while digital marketing reduces promotion costs by 70% and increases revenue, micro-enterprises particularly struggle with systematic implementation, often adopting fragmented approaches that fail to maximize platform capabilities. Hanum (2024) corroborates these findings, demonstrating that entrepreneurial orientation alone insufficiently drives performance without mediated social media adoption strategies, highlighting the necessity of structured digital marketing frameworks. The specific challenges confronting micro-enterprises in the digital marketing domain require targeted investigation. Suryani (2023) enumerates persistent obstacles including technical skill deficiencies, financial limitations, and difficulties in maintaining content consistency. Micro-enterprises specializing in digital services, such as mobile top-up businesses, face additional complexities in establishing credibility and differentiating themselves within saturated markets (Permatasari, 2024). Swastika (2025) documents that MSMEs implementing Instagram Ads experienced follower growth from 833 to over 1,000 within six months and increased customer interactions from 50 to 70 per post, yet acknowledges that sustained success demands continuous content innovation and responsive customer engagement. These findings underscore the critical need for context-specific digital marketing models tailored to the operational realities and resource constraints of micro-scale service providers. This research addresses these gaps by implementing and evaluating a comprehensive digital marketing strategy for Khoirul.topup, a micro-enterprise providing mobile top-up and digital payment services, utilizing Instagram as the primary promotional platform. The study's objectives are threefold: to systematically implement digital marketing through Instagram business account optimization, strategic content creation, and performance evaluation using Instagram Insights; to assess the platform's effectiveness in expanding promotional reach and enhancing customer interaction; and to identify implementation challenges and develop evidence-based solutions. The urgency of this investigation is amplified by Indonesia's accelerating digital economy, where micro-enterprises must rapidly adapt to remain viable (Rahmawati, 2025). This study's novelty lies in its focused examination of Instagram marketing within the specific context of digital service micro-enterprises, providing a replicable implementation framework that integrates visual branding, interactive content strategies, and direct transaction facilitation through Instagram's direct messaging feature, thereby contributing empirical insights to the limited literature on micro-enterprise digital transformation in service sectors.